Responses of performance and differential leukocyte count to methionine and threonine supplementations on broiler chickens challenged with infectious bursal disease in tropical condition - Maroufyan, Elham; Kasim, Azhar; Hashemi, Seyed Reza; Loh, Teck Chwen; Bejo, Mohd Hair (Knowledgia Review, Malaysia, 2010)
The aim of this study was to find the effect of methionine and threonine supplementations higher than the NRC recommendation on growth performance and white blood cell differentiation of broiler chickens challenged with infectious bursal disease. A total of 450 day-old male broiler chicks were assigned to nine groups. Chickens were fed by three graded levels of DL- methionine [NRC (M1), 2 times NRC (M2) and 3 times NRC (M3)] and three graded levels of L-threonine [NRC (T1), 2 times NRC (T2) and 3 times NRC (T3)] from day 1-42 of age. On day 28, all birds were challenged with a commercial live-IBDV vaccine. Body Weight Gain (BWG) and Feed Intake (FI) and Feed Conversion Ratio (FCR) were significantly influenced by the dietary treatments before challenge and either methionine or threonine at the highest levels significantly decreased BWG, FI and FCR in broiler chickens. Birds were fed with M3T3 had the lowest body weight gain after challenge. Supplementation of two times methionine and threonine (M2T2) to the diet decreased peripheral blood heterophils and increased lymphocytes and H/L ratio on day 28. On day 42, complete white blood cell tended to increase with increasing level of methionine supplementation. Threonine did not affect peripheral blood differential leukocyte count of broiler chickens. In conclusion, our data suggest that the methionine and threonine requirement of male broiler chicks is higher for growth performance than was suggested by the last NRC committee and methionine and threonine higher than NRC requirements in tropical condition can ameliorate the negative effects of heat stress.